Repozitoriji učnega gradiva kot podpora bolonjskemu procesu - Jelušić, Srećko (Organizacija znanja, 2006)
This paper argues that the application of new teaching methods together with quality assessment of higher education institutions depend directly on the quality of teaching aids and services available to both stuents and teachers. For that purpose it is necessary to ensure the co-operation between teachers, pedagogues, librarians and information and telecommunication professionals during the application of, so called, Bologna curricula. The aim of this paperis to describe the progress in the creation of the repository of teachingmaterials i.e. the application of the course management system and to present the plans of the University departments in the area of information sciences in Croatia in relation to the education of future generations of information professionals, with a particular emphasis on the development of their abilities to co-operate with teachers and ICT professionals in creation,maintenance and usage of the repository of teaching materials as wellas the appropriate tools managing the learning process.
Keywords: bolonjski proces; Croatia; Hrvaška; informacijski viri; repozitoriji; učno gradivo; visokošolske knjižnice